Nicaragua : Staff Report for the 2002 Article IV Consultation and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and for Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper assesses Nicaragua's 2002 Article IV Consultation and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and for Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). A key program objective is medium-term fiscal sustainability. This will require a significant reduction of primary spending, while protecting poverty-reducing outlays, and an increase in tax revenues. The IMF staff recommends that the authorities' request for a new three-year PRGF arrangement and interim HIPC assistance be approved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet